Continuum modeling for neuronal lamination during cerebral morphogenesis considering cell migration and tissue growth. Issue 7 (19th May 2021) - Takeda, Hironori; Kameo, Yoshitaka; Adachi, Taiji
Abstract: For neuronal lamination during cerebral morphogenesis, later-born neurons must migrate through already-accumulated neurons. This neuronal migration is biochemically regulated by signaling molecules and mechanically affected by tissue deformation. To understand the neuronal lamination mechanisms, we constructed a continuum model of neuronal migration in a growing deformable tissue. We performed numerical analyses considering the migration promoted by signaling molecules and the tissue growth induced by neuron accumulation. The results suggest that the promoted migration and the space ensured by tissue growth are essential for neuronal lamination. The proposed model can describe the coupling of mechanical and biochemical mechanisms for neuronal lamination.